Study of the potential anti-inflammatory properties of a new remedy based on a dicarboxylic acid derivative in the conditions of toxic hepatitis - Morozyuk, Anastasia (ScienceRise: Biological Science, 2025)
The aim of the study is to investigate changes in the level of C-reactive protein in the blood serum of rats under the conditions of carbon tetrachloride-induced hepatitis and its correction with a new agent based on a dicarboxylic acid derivative and a selenium-containing compound. Materials and methods. The study was conducted on outbred white rats weighing 200-250 g in compliance with all principles of ethical treatment of animals. The model of toxic hepatitis was reproduced by subcutaneous administration of carbon tetrachloride (CCl4) at a dose of 4.5 ml/kg b.w. (50% solution in oil) three times a week for a month. The animals were divided into groups: I – control, which was injected with a solvent (2% starch solution); II – rats with paracetamol-induced hepatitis; III – rats with hepatitis, which received a new agent based on a dicarboxylic acid derivative and a selenium-containing compound at a dose of 32 mg/kg b.w. to correct liver pathology. The content of C-reactive protein in the blood of animals was studied by enzyme-linked immunosorbent assay using the appropriate set of reagents according to the manufacturer's instructions. Results. Significant changes in the level of C-reactive protein were recorded in animals from the induced hepatitis group compared to intact control animals, as well as structural changes in the liver tissue of animals with induced hepatitis compared to intact control animals. The use of the new agent for correction led to the normalization of indicators. Conclusions. In the conditions of prolonged tetrachloromethane-induced hepatitis, a significant increase in the content of C-reactive protein in the serum of rats from the group "Hepatitis" compared to animals of intact control was recorded. The use of the new remedy based on the derivative of dicarboxylic acid and a selenium-containing compound for the correction of the pathology leads to a significant decrease in the level of C-reproductive protein in animals’ blood serum. It has been shown that the new derivative of dararboxylic acid and selenium-containing compound in conditions of toxic hepatitis has a playhotropic effect in the form of hepatoprotective, spermatomoodulatory and anti-inflammatory activity